2009
DOI: 10.1017/s0144686x09990365
|View full text |Cite
|
Sign up to set email alerts
|

Sharing stories: a meta-ethnographic analysis of 12 autobiographies written by people with dementia between 1989 and 2007

Abstract: People with dementia are finding increasingly creative and diverse ways of making their voice heard in society and one such method is through the publication of autobiographical accounts. Following set inclusion criteria, this meta-ethnographic analysis compares and contrasts the contents of 12 books written by people with dementia and published between 1989 (the year of publication of the first text) and the end of 2007 (the selected cut-off point for inclusion). Of the 12 books, three authors were published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…People with dementia have, by definition, significant impairments in two or more cognitive domains, such as memory, attention, perception, language and executive function, which necessarily impacts on an individual's ability to participate in, or engage with, research. Yet today the voice of the person with dementia is heard increasingly, in personal testimony, public consultation, service development and research . Core principles for involving people with dementia in research have been co‐created, and barriers and enablers to the engagement of people with dementia in research have been identified .…”
Section: Introductionmentioning
confidence: 99%
“…People with dementia have, by definition, significant impairments in two or more cognitive domains, such as memory, attention, perception, language and executive function, which necessarily impacts on an individual's ability to participate in, or engage with, research. Yet today the voice of the person with dementia is heard increasingly, in personal testimony, public consultation, service development and research . Core principles for involving people with dementia in research have been co‐created, and barriers and enablers to the engagement of people with dementia in research have been identified .…”
Section: Introductionmentioning
confidence: 99%
“…It is known from qualitative research involving those at the onset of their condition (Robinson, Ekman, Meleis, Winblad, & Wahlund, 1997;Steeman, de Casterlé, Godderis, & Grypdonck, 2006;Alzheimer's Society, 2010a,b;McCleary et al, 2013), influential reports (All-Party Parliamentary Group, 2012) and from the autobiographies written by people living with dementia (for a review see: Page & Keady, 2010), that the first subtle signs of onset are often difficult for the person to understand and translate into their everyday frames of reference and meaning-making. As an illustration, at the end of the 1980s in the first book written by a person with dementia, the Reverend Robert Davis described his initial encounter with (undiagnosed) dementia as follows: 'Deep within me I knew that something was terribly wrong with my mental processes' (Davis, 1989 p.49).…”
Section: Introductionmentioning
confidence: 99%
“…In these instances they are often young and well educated, usually, and often of necessity, not living with the most challenging aspects of this condition. Page and Keady (2010) suggest that there remains a tendency to privilege male and middle class voices over poorly educated female ones. There is scant literature on the expressed experiences of people living with dementia in non-Western cultures (Mazaheri et al 2013), and as already stated the argument we present here is grounded in a Western perspective and draws on Western literature.…”
Section: Dichotomising Dementiamentioning
confidence: 99%